2021
DOI: 10.1200/go.20.00542
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on Oncologists: Results of an International Study

Abstract: PURPOSE As frontline workers facing the COVID-19 pandemic, healthcare providers should be well-prepared to fight the disease and prevent harm to their patients and themselves. Our study aimed to evaluate the knowledge, attitude, and practice of oncologists in response to the COVID-19 pandemic and its impact on them. METHODS A cross-sectional study was conducted using a validated questionnaire disseminated to oncologists by SurveyMonkey. The tool had 42 questions that captured participants’ knowledge, attitude,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 30 publications
1
21
0
1
Order By: Relevance
“… 42 High levels of collegiality, cooperation, and positive coworker relationships were noted as positive impacts in an international study of oncologists. 29 Our findings support these tenets and suggest implementing frequent communication, structured debriefing, policies to protect staff safety, procedural algorithms, and psychological support can balance out negative impacts on HCPs across resource settings.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“… 42 High levels of collegiality, cooperation, and positive coworker relationships were noted as positive impacts in an international study of oncologists. 29 Our findings support these tenets and suggest implementing frequent communication, structured debriefing, policies to protect staff safety, procedural algorithms, and psychological support can balance out negative impacts on HCPs across resource settings.…”
Section: Discussionsupporting
confidence: 70%
“… 1 , 25 Ultimately, decreased availability of pediatric oncology providers during the pandemic could lead to a long‐term scarcity in the workforce, particularly in LMICs where multidisciplinary staff and specialty training opportunities are limited. 14 , 28 To mitigate this, health care organizations should consider implementing policies to retain professionals in their trained specialty 29 and build a relief pool of providers. 30 Enacting such policies will both lessen the effect of acute shortages due to illness or quarantine and prevent long‐term deficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…Xiong et al did research on how students in Mainland China and Hong Kong conceive overseas studies plans against the COVID-19 crisis, using the method of distributing the questionnaires via online survey systems (Qualtrics and Wenjuanxing) to the above two groups of students, which led to a conclusion that the pandemic has not only significantly decreased international student mobility but is also shifting the mobility flow of international students. The research team also found that the global health crisis would intensify social and economic inequalities across higher education systems [1]. Mok et al have studied the affection of pandemic of COVID-19 for mobility and perspective of international students, adopting a method that investment a bunch of different the information of survey and statistic such as Institute of International Education and many other surveys to support detail numbers and data to the report and the essay.…”
Section: The Limit and Restriction In Mobility Of International Studentsmentioning
confidence: 99%
“…Various studies in the initial phase of the pandemic had raised severe psychosocial and professional concerns for the entire radiation oncology fraternity. 6 , 14 , 16 - 18 However, the actual impact of the pandemic on RTTs has largely been underestimated. Also, the impact at the time of withdrawal of restrictions and introduction of various vaccination strategies has never been evaluated.…”
Section: Introductionmentioning
confidence: 99%